POLITICAL ANALYSIS OF THE LEGAL INCREASE IN VALUE-ADDED TAX (VAT) RATES IN THE NATIONAL ECONOMIC RECOVERY - Intan Sari, Savira; Hartono Paulus, Darminto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Corona Virus Disease (COVID-19) has been designated as a global pandemic since March 11, 2020, by the World Health Organization (WHO). COVID-19 is a national disaster in the Presidential Decree of the Republic of Indonesia Number 12 of 2020 concerning the determination of non-global disasters related to the spread of coronavirus disease (COVID-19). The massive transmission of COVID-19, designated as a global pandemic, has impacted various strategic sectors, including the international and national economic sectors. Therefore, this study examines the legal politics of the increase in Value Added Tax (VAT) rates in the recovery of the national economy affected by the global COVID-19 pandemic. The research uses normative juridical descriptive, statutory, and conceptual approaches from primary and secondary legal sources. The results of this study indicate that the legal politics of increasing Value Added Tax (VAT) rates is an inappropriate and risky national economic recovery strategy because it can cause inflation in a national economy that has not fully recovered. In the context of national economic recovery, efforts to suppress state spending are more efficient than increasing Value Added Tax (VAT), which is prone to risk.